Active Steerable Catalytic Supraparticles Shuttling on Preprogrammed Vertical Trajectories. Issue 15 (23rd May 2016) - Sperling, Marcel; Kim, Hyung‐Ju; Velev, Orlin D.; Gradzielski, Michael
Abstract : This study presents a novel type of mm‐sized colloidal supraparticle performing self‐propelled oscillating motion that can be programmed on a controlled 3D trajectory. These supraparticles are self‐assembled inside drying aqueous colloidal suspension droplets on a superhydrophobic surface. The droplets contain silica microspheres as main colloidal building block and Pt‐covered Fe3 O4 nanoparticles as catalyst. The supraparticles are rendered patchy by attracting the magnetic catalyst nanoparticles to one side of the droplet during the assembly. Catalytic decomposition of H2 O2 leads to vertical motion by buoyancy of formed bubbles. This study comprehensively analyzes this motion in terms of the vertical oscillation frequency that depends on H2 O2 "fuel" concentration as well as on the supraparticles density. It is demonstrated that the magnetic functionality can be used to manipulate the particle's trajectory to access nearly any place within the vessel. Furthermore, after binding of α‐amylase to the particle surface it is shown that their motion leads to rapid catalytic decomposition of a blue starch–iodine complex within the whole medium. Thus, these functional supraparticles can find versatile applications in a new generation of highly efficient catalysts, microstirrers and self‐motile microshuttles that can perform designed tasks while being able to access every point in the liquid in controlled trajectories. Abstract : This study describes the preparation of mm‐sized self‐propelling elevator supraparticles with a catalytically active patch able to perform oscillating elevator motion, where the trajectories can be controlled by magnets. These supraparticles able to explore full 3D‐space, are then shown to be able to perform chemical tasks, as demonstrated for the case of decomposing starch on its trajectory.